PRE-PARTURITION MOVEMENT PATTERNS AND BIRTH SITE CHARACTERISTICS OF MOOSE IN NORTHEAST MINNESOTA - McGraw, Amanda M.; Terry, Juliann; Moen, Ron (Lakehead University, 2014)
Habitat used immediately after parturition is important to survival of moose calves, though different habitat types may be functionally similar and thus contribute to the variability in habitat use reported in the literature. Neonates are relatively immobile, which restricts movement of the cow-calf pair and makes both vulnerable to predation. The cow also requires adequate access to forage during the period when calf mobility is limited. We used fine-scale movement data to determine linear distance traveled to the birth site as well as habitat use by cow-calf pairs in northeast Minnesota. All cows made long distance movements (x = 6 km) to the birth site where they localized in 1.72 ± 0.48 ha (95% kernel polygon) for approximately 7 ± 0.7 days. A mosaic of cover types that reflected availability across the landscape were used by the cow prior to localization at the birth site. Birth site areas consisted of one cover type rather than the mosaic used before birth, and varied among cows, though bogs were used most often (40%). The small birth site area and use of bog habitat were likely a consequence of low calf mobility post-parturition. Upon exiting the birth site, cow-calf pairs shifted toward use of mixed and young/regenerating forest which likely reflects the need and use for highly nutritious browse to meet the high energetic cost of lactation.